Dedica onoraria per Tolemeo III e Berenice - Mirizio, Giuditta (Axon, 2017)
Inscription in honour of the king Ptolemy III and his wife, the queen Berenice II, on behalf of the inhabitants of Falasarna. It is formulated according to the structure of a votive dedication and consecreted to the Great Gods, the Cabiri, on the basis of the most plausible interpretation.